Synergy of Islamic Religious Education Teachers with People Students' Parents in Cultivating Morals in Students at SMPN 11 Baubau - Susiana, Susiana; Basri, Basri; Jusu, La (Journal of English Language and Education, 2025)
The purpose of this research is to characterize and examine how parents and Islamic Religious Education (IRE) instructors work together to inculcate moral principles in seventh-grade children at SMP Negeri 11 Baubau. One essential component of Islamic education is the development of moral character, which is the duty of both parents and instructors at home. Therefore, to guarantee the continuity and consistency of moral instruction for pupils, a cordial partnership between educators and parents is crucial. This study uses a case study methodology with a qualitative approach. Documentation, in-depth interviews with IRE parents and teachers, and observations were used to gather data.